The postwar development of Japanese studies in the United States - Hardacre, Helen, 1949- (Leiden : Boston : Brill, 1998)
The present volume documents the postwar history of United States scholarship on Japan. A careful selection of North American scholars under the general editorship of Helen Hardacre shows that a range of factors have directed Japanese studies in the United States since 1945. Among these factors are social and political change in Japan and the United States, shifts in dominant scholarly concerns about Japan, and changing evaluations of area studies. The general aim of the volume is to put current debates in historical perspective and to help assessing the field's achievements. It identifies areas requiring more work and charts directions for the future.
Includes bibliographical references and index.
Keywords: Japan -- Study and teaching -- United States